Potential alternative tree species to Fraxinus excelsior in European forests - Lévesque, Mathieu; Bustamante Eduardo, José Ignacio; Queloz, Valentin (Frontiers in Forests and Global Change, 2023)
Common ash (Fraxinus excelsior L.) is a keystone tree species in Europe. However, since the 1990s, this species has been experiencing widespread decline and mortality due to ash dieback [Hymenoscyphus fraxineus (T. Kowalski) Baral, Queloz and Hosoya]. Besides H. fraxineus, emerald ash borer (Agrilus planipennis Fairmaire), an invasive alien pest already devastating ash trees in western Russia, is spreading westward and becoming an emerging threat to the remaining European ash populations. While efforts to control ash dieback continue to be a priority, it is becoming crucial to compensate for the loss of ash and its ecosystem services by elaborating restoration strategies, including the search for alternative native and non-native tree species. This review summarizes available knowledge on potential alternative tree species to common ash to help forest managers to cope with ash dieback. Although using natural regeneration and promoting tree species diversity can reduce the impacts of ash dieback in European forests, our review indicates that no native species alone or in combination can fully replace the ecological niche of common ash and its associated ecosystem services (e.g., biodiversity and timber). To fill this gap, forest managers have considered using non-native ash species that are tolerant to both H. fraxineus and A. planipennis and have similar ecological and forestry values as common ash. Of the 43 ash species reviewed, few non-native ash species (e.g., Fraxinus mandshurica Rupr. and Fraxinus platypoda Oliv.) have similar ecological characteristics to common ash and are tolerant to H. fraxineus and A. planipennis. However, the performance of non-native ash species in European forests, their invasiveness potential, and the risk of hybridization with native ash species are still unknown. With the current state of knowledge, it is thus too early to recommend the use of non-native ash species as a suitable option to deal with ash dieback. The priority should be the conservation, regeneration, and breeding of tolerant common ash populations to H. fraxineus, as well as the use of the natural regeneration of other native tree species. Our review highlights the need for controlled experimental plantations to better understand the regeneration ecology and invasiveness potential of non-native ash species prior to their utilization in natural forests.